Situation Report: Czechoslovakia, 21 April 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Jaruzelski in Prague Charter 77 Speaks Out Again New Regulations on Sales by Private Persons The Right People for the Wrong Jobs, or the Other Way Around Investment Policy in Industry Economic Miscellanea Swimmers Defect